189k views
2 votes
Find the product of (a + b + c) and (a + b)​

User Jzqa
by
5.2k points

2 Answers

0 votes

Answer:


a^2+b^2+2ab+ac+bc

Explanation:


(a+b+c(a+b)=\\a^2+ab+ac+ab+b^2+bc=\\a^2+b^2+ab+ab+ac+bc=\\a^2+b^2+2ab+ac+bc

User Andrew Daniel
by
5.6k points
3 votes

Answer:

a² + 2ab + b² + ac + bc

Explanation:

(a + b + c) * (a + b) = aa + ab + ac + ba + bb + bc

= a² + 2ab + b² + ac + bc

The trick you use here is called the distributive property.

User Albana
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.